2017
DOI: 10.1093/sleep/zsx142
|View full text |Cite
|
Sign up to set email alerts
|

A Greater Extent of Insomnia Symptoms and Physician-Recommended Sleep Medication Use Predict Fall Risk in Community-Dwelling Older Adults

Abstract: The number of insomnia symptoms predicts 2-year fall risk in older adults. Taking physician-recommended sleep medications increases the risks for falling in older adults, irrespective of the presence of insomnia symptoms. Future efforts should be directed toward treating insomnia symptoms, and managing and selecting sleep medications effectively to decrease the risk of falling in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…Notably, taking sleeping pills and performing irregular or regular physical exercise were not independently correlated with falls in the three waves of surveys, and these findings contradict those of two large published studies [47,48] and the updated review of exercise as a single intervention for preventing falls [49]. It could be due to bias in data collection, since we did not collect information about fall-related medication dosage and detailed intensity, duration, and type of exercise.…”
Section: Discussioncontrasting
confidence: 70%
“…Notably, taking sleeping pills and performing irregular or regular physical exercise were not independently correlated with falls in the three waves of surveys, and these findings contradict those of two large published studies [47,48] and the updated review of exercise as a single intervention for preventing falls [49]. It could be due to bias in data collection, since we did not collect information about fall-related medication dosage and detailed intensity, duration, and type of exercise.…”
Section: Discussioncontrasting
confidence: 70%
“…Physical activity (PA) can reduce insomnia symptoms and enhance sleep quality [ 17 , 18 ]; however, menopausal elderly women have muscle weakness, which may lead to reduced PA [ 19 , 20 ]. In addition, previous studies reported insomnia symptoms and sleep disturbances are associated with the falling risk in elderly adults [ 21 , 22 ]. Thus, elderly women with insomnia may impose a potential societal cost [ 12 , 23 ], which may decrease the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that taking sleeping pills and getting physical exercise either irregularly or regularly were not independently correlated with falls in the three waves of surveys, and these findings contradict those of two large published studies [33,34] and the updated review of exercise as a single intervention for preventing falls [35]. Further studies are needed to clarify this discrepancy.…”
Section: Discussionmentioning
confidence: 77%